2018
DOI: 10.1111/irv.12618
|View full text |Cite
|
Sign up to set email alerts
|

Underweight, overweight, and obesity as independent risk factors for hospitalization in adults and children from influenza and other respiratory viruses

Abstract: BackgroundThe relationship between obesity and risk of complications described during the 2009 influenza pandemic is poorly defined for seasonal influenza and other viral causes of influenza‐like illness (ILI).MethodsAn observational cohort of hospitalized and outpatient participants with ILI was conducted in six hospitals in Mexico. Nasopharyngeal swabs were tested for influenza and other common respiratory pathogens.ResultsA total of 4778 participants were enrolled in this study and had complete data. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
138
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 30 publications
7
138
1
12
Order By: Relevance
“…Based on the first epidemiological studies on the SARS-CoV-2 virus, it appears that co-morbidities such as diabetes mellitus and hypertension increase the risk for development of acute respiratory distress syndrome [60]. Additionally, obesity has been described as an independent risk factor for hospitalization in respiratory viral infections, including coronaviruses [61]. Therefore, it can be expected that a relatively large portion of the critically ill COVID-19 patients are (morbidly) obese.…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…Based on the first epidemiological studies on the SARS-CoV-2 virus, it appears that co-morbidities such as diabetes mellitus and hypertension increase the risk for development of acute respiratory distress syndrome [60]. Additionally, obesity has been described as an independent risk factor for hospitalization in respiratory viral infections, including coronaviruses [61]. Therefore, it can be expected that a relatively large portion of the critically ill COVID-19 patients are (morbidly) obese.…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…Since the "Spanish" influenza pandemic of 1918, it is known that malnutrition (both underand over-nutrition) is linked to a worse prognosis of the viral infection [1]. The 1957-1960 "Asian" and the 1968 "Hong Kong" influenzas confirmed that obesity and diabetes lead to a higher mortality as well as a more prolonged duration of illness even if the subjects were without other chronic conditions that increase the risk of influenza-related complications [2,3]. During the 2009 Influenza A virus (IAV) H1N1 pandemic, obesity was also linked to increased risk of severe disease and a risk factor for hospitalization and death [4].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced age is a well-recognized risk factor for development of severe disease [1,2], however the impact of obesity on disease severity has not been thoroughly explored. Obesity was associated with increased severity and mortality in pandemic H1N1 influenza and other respiratory viruses [3,4].…”
mentioning
confidence: 99%